Dynamic simulation and experiments of a low-cost small ORC unit for market applications. (1st October 2019) - Carraro, Gianluca; Rech, Sergio; Lazzaretto, Andrea; Toniato, Giuseppe; Danieli, Piero
Highlights: The potential of a micro-scale ORC system to enter the market is evaluated. The dynamic behaviour of the unit is analysed with simulations and experiments. Tests show prompt reaction of the unit to variations of the heat source temperature. The dynamic model shows errors lower than 6.6% in the prediction of measurements. The investment cost (lower than 2500 €/kW) makes the unit appealing to the market. Abstract: Organic Rankine Cycle is one of the most efficient, profitable and feasible technology for low-to-medium temperature heat recovery. The boost to the development of small-scale systems that could easily enter the market poses challenges in the design and selection of components, and in the choice of the operating conditions. This work deals with a micro-scale Organic Rankine Cycle (ORC) unit that has been designed to be cheap, efficient and compact, and tested to analyze performance and transient response under large variations of the heat source temperature. A dynamic model is also built and validated against two sets of experimental data: the first one refers to maximum power operation of the system and the second one to partial load operation close to the occurrence of two-phase expansion. The goal is to understand the potential of the system to face market applications, for which best design choices, operational limits and response time to variable heat sources must be identified. The choice of scroll expander, volumetric pump and plate heat exchangers has been made according to the lowest cost-to-efficiency ratio to keep the investment cost below 2500 euro/kW, already in the pre-market phase, in the power range of 3–4 kW. Results of the experiments show a fast time response, with a prompt reaction of the system to variations of the heat source temperature. Simulations demonstrated the ability of the model to capture with good accuracy the system dynamics. In particular, the validation process at maximum power operation (expander power output of 3300 W) shows maximum relative errors of about 4% in the prediction of measurements, whereas, the validation process at partial load operation yields slightly higher errors, namely 5.2% and 6.6% in the prediction of the evaporation pressure and the expander power output, respectively.